Post-Merger Corporate Performance: A Case of NIB Bank Pakistan. - Fareeha Batool; Misaal Naeem (SEISENSE Journal of Management, 2018)
This study measures whether the mergers generate efficient, trustworthy and wide-ranging capital base for the bank that completely comprised mergers and to what range mergers of banks increase the confidence of the investors, the customers, the shareholders and capacity to finance the real time sector. For the purpose total 9 ratios under profitability ratios and other ratios applied on key financial figures to analyze the selected bank performance. Key figures were taken from the website of the NIB bank. Data was taken from 2004-07 before merger and 2008-12 after the merger.